Unmet needs among disabled elderly Malaysians - Momtaz, Yadollah Abolfathi; Tengku Abdul Hamid, Tengku Aizan; Ibrahim, Rahimah (Elsevier, 2012)
Unmet need as a significant factor affecting quality of life in later life has recently received considerable attention in gerontological research. The main aim of this study was to identify the prevalence, predicting factors, and negative consequence of unmet need among older Malaysians. The findings may be useful to reduce unmet need and the burden of its adverse consequence. The sample for this study consists of 400 functionally disabled elderly people aged 60 and over was obtained from a large national survey. Unmet need was operationally defined based on Manton’s (1989) criteria. The findings from the present study showed about 18.0% of functionally disabled older Malaysians suffer from unmet need. Logistic regression revealed that gender (being male) and chronic health conditions are statistically associated with increased odds of unmet need after adjusting for other possible risk factors. Further results indicated that unmet need statistically increases odds of fall as a negative consequence of unmet need. The high prevalence rates of unmet need among disabled elderly men and chronically ill older persons suggest that policy makers should pay more attention to this vulnerable group to achieve good quality of life. The implications and limitations of the present study are discussed.